Physical activity maintenance and increase in Chinese children and adolescents: the role of intrinsic motivation and parental support - Liu, Yujie; Ge, Xin; Li, Huilun; Zhang, Erliang; Hu, Fan; Cai, Yong; Xiang, Mi (Frontiers in Public Health, 2023)
Objective: This longitudinal study aimed to examine the association of intrinsic motivation, parental physical activity, and parental support with physical activity maintenance and increase among children and adolescents. Methods: A sample of 2,424 children and adolescents in Shanghai, China participated in the two-wave survey before and during the COVID-19 pandemic. The questionnaire measured children and adolescents’ physical activity and intrinsic motivation, as well as their parents’ physical activity and support (concern for their child and co-activity with their child). Multivariable logistic regressions were performed by groups to examine the associations between these factors and physical activity change. Results: Most children and adolescents exhibited a decline in physical activity participation during the pandemic, as indicated by a mere 15.0% and 8.0% of individuals maintaining and increasing their pre-pandemic levels, respectively. Among the initially active participants, perceived self-choice (OR = 1.341 [95%CI: 1.173-1.533]) and parental concern (OR = 1.922 [95%CI: 1.204-3.068]) predicted maintained physical activity. Increased physical activity was predicted by perceived enjoyment (OR = 1.193 [95%CI: 1.046-1.362]) and parental co-activity (OR = 1.995 [95%CI: 1.095-3.633]). Conclusions: This study provides longitudinal evidence that intrinsic motivation and parental support can have a positive impact when physical activity levels change significantly. Effective interventions targeting multilevel factors are needed to maintain or increase children and adolescents’ physical activity.